Theodore Abū Qurra and the Instability of “Heresy” - Mugler, Joshua (Medieval encounters, 2015)
Theodore Abū Qurra, a Chalcedonian bishop in late eighth- and early ninth-century Harran, attempts to defend Christianity rationally against the new intellectual power of Islam. However, in his classification of the world’s religions, he places non-Chalcedonian Christians in a strange category called “heresy.” They are both within Christianity and without, sitting precariously on the border between Theodore’s Christianity, the “one true religion,” and its false counterparts. Nevertheless, Theodore reserves some of his harshest rhetoric for these heretics, viewing them as a sickness infecting the Church; he even implies that it is acceptable for the emperor to persecute them, though he elsewhere writes that Christianity is never spread by power or force. This paper addresses this odd term, “heresy,” and its ability to destabilize Theodore’s neat classification of religions. Perhaps this destabilization itself leads to his harsh attacks, as he seeks for stability in a world newly destabilized by the advent of Islam.